Relatório de estágio supervisionado : uma análise das interações entre o estagiário, o professor supervisor e o professor orientador - Meireles, Amanda Alves Lino de (2017)
The present work whose title is called Supervised Internship Report: an analysis of the interactions between the Trainee, the Supervisory Teacher and the Advisor, aims to observe and analyze the interactions of all subjects involved in the internship from reports of Internship Supervised. In addition to the interactions, we will also analyze the perceptions and sensations of the enlightened subjects. We used as corpus five reports presented to the discipline of Supervised Internship IV in the year 2016 of students trainees of the course of Letters of the Federal University of Paraíba. These are placements carried out in public schools in Paraíba. As a theoretical basis To base our work, we use the authors Mendes and Castro (2008), Kleiman (1995), Fávero (1992), Fiorentini e Castro (2003), Almeida e Pimenta (2014) Pimenta e Lima (2009) and others so that we can relate our work to the conceptions about the stage that these authors bring on the basis of studies and experiences. This work allowed us to reflect on the importance of the internship in the lives of all involved in this process, as well as brought us to live and experience experiences that only added in our academic and professional lives.